3x-5=4

To remove the radical on the left side of the equation, square both sides of the equation.

3x-52=42

Multiply the exponents in ((3x-5)12)2.

Apply the power rule and multiply exponents, (am)n=amn.

(3x-5)12⋅2=42

Cancel the common factor of 2.

Cancel the common factor.

(3x-5)12⋅2=42

Rewrite the expression.

(3x-5)1=42

(3x-5)1=42

(3x-5)1=42

Simplify.

3x-5=42

Raise 4 to the power of 2.

3x-5=16

3x-5=16

Move all terms not containing x to the right side of the equation.

Add 5 to both sides of the equation.

3x=16+5

Add 16 and 5.

3x=21

3x=21

Divide each term by 3 and simplify.

Divide each term in 3x=21 by 3.

3×3=213

Cancel the common factor of 3.

Cancel the common factor.

3×3=213

Divide x by 1.

x=213

x=213

Divide 21 by 3.

x=7

x=7

x=7

Solve for x square root of 3x-5=4